INTEGRASI TEKNOLOGI DAN KURIKULUM DALAM PENDIDIKAN: ANALISIS TREN DAN INOVASI TERKINI: INTEGRATION OF TECHNOLOGY AND CURRICULUM IN EDUCATION: AN ANALYSIS OF RECENT TRENDS AND INNOVATIONS - Fathurrahman, Muhammad; Ismail Djakaria; Sarira, Regina Amelia (Universitas Muhammadiyah Sorong, 2024)
This bibliometric analysis investigates trends in publications linking